Detection of Quorum Sensing Signal Molecules and Identification of espB and Crt4 genes among Biofilm Forming of Citrobacter freundii - Wathiq Abbas Hatite Al-Daraghi1, Mautham Khazaal Kadhim AL-Behadili1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
150 samples from different clinical sources were collected from October 2018 to March 2019 from three hospitals in Maysan: Al Sadr General Education Hospital, Al Zahrawi Surgical Hospital and Maternity and Child Hospital to demonstrate the spread and distribution of Citrobacter freundii in several hospitals in Maysan. All isolates were identified based on morphological characteristics and biochemical tests. Results were confirmed by Api 20 E and Vitek 2 compact. A total of 14 isolates (9.3%) of 150 were found to be Citrobacter freundii. The isolates were considered as acute diarrhea in children, UTI, burns, wounds and most frequent ear swabs. PCR results showed that the LuxR 428bp genes were present in the Citrobacter freundii bacteria identified by previous diagnostic methods and this confirms the accuracy of the tests and methods used to determine this type.